TINDAK TUTUR DIREKTIF GURU DALAM PROSES BELAJAR MENGAJAR DI TAMAN KANAK-KANAK BUNDA NINIK S. ANANDA DI DESA LECES KABUPATEN PROBOLINGGO - Tiara Dewi Rusmila; Bambang Wibisono; Edy Hariyadi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2019)
Kindergarten Education emphasizes the provision of educational stimuli to help the growth and development of children. The teacher is a teacher or educator in charge of educating, teaching, guiding, directing, training, evaluating, and evaluating students. Based on this, the teacher is obliged to teach in a way and in good media. One of them is a good way of speaking, especially when the teacher gives orders, invitations, suggestions, explanations, requests, statements, praise and advice to his students. In kindergarten is an introduction, namely the introduction of numbers and letters. In addition, teachers are required to be able to stimulate and facilitate the development of the language of their students. Therefore, the teacher must be creative in acting speech. That is, the teacher must be clever in processing a speech so that learning can run effectively. Teacher's speech in Kindergarten must be interesting and in accordance with the psychological level of the student. Attractive speeches will be absorbed well by students so that targeted learning is achieved.